Pengembangan Pola Pikir Ekonomi Produktif pada Siswa SMK sebagai Persiapan Menghadapi Dunia Kerja dan Kewirausahaan - Wardyatul Fuady Harahap; Yunanda Eka Putra; Akman Daulay (Lembaga Pengembangan Kinerja Dosen, 2026)
The increasingly competitive world of work and business demands that young people develop a productive economic mindset from an early age. This study aims to analyze the importance of strengthening a productive economic mindset for vocational high school students in preparing them to enter the world of work and business. The activities included theoretical training, such as workshops, and digital marketing simulations using social media. The results showed a 56% increase in student understanding and a significant transformation in entrepreneurial mindsets across eight key aspects: growth mindset, innovation, resilience, adaptability, risk-taking, proactivity, creativity, and visionary thinking. This study used a qualitative descriptive approach using observation, interviews, and a literature review. The results indicate that economics learning activities and the entrepreneurship program contribute positively to the development of a productive, creative, and independent mindset in students. By strengthening this mindset, students are not only oriented towards being job seekers but also have the potential to become job creators.